A Brief Study on the Speech Assessment of the Children Suffering from Cerebral Palsy - Garg, Neha (Gipan, 2025)
The present study attempts to assess the ability of the children affected with cerebral palsy whether they can be able to articulate accordingly in such a way that other people can understand. The paper also tries to assess how well they can be able to differentiate the meaning relations. All the twenty children participated in the study were affected with cerebral palsy, in which two children were athetoid and all the others were spastic. This paper also describes the major linguistic features demonstrated by the CP affected children exposed to Hindi speaking environment. The paper reveals that the gross motor function in children with CP is importantly linked with the skill to communicate and thus it is very much significant to take into consideration. Usually the children with disorders in the speech have difficulties using the consonant production and often cause dysarthria. By knowing the ratio of children with CP affected with articulation problems and the skills to acquire the meaning values, it will be easier to give the proper treatment, which would enhance the various disorders in the children affected with cerebral palsy. Using a picture-naming task with 35 common words, the study assessed the articulation and semantic comprehension of 20 Hindi-speaking children with CP. Key findings indicate a strong correlation between motor function and intelligibility, with significant difficulties in producing aspirated consonants and consonant clusters. The study underscores the need for future research to develop language-specific, motor-learning-based intervention programs to improve speech outcomes.